Pengembangan Media Science Crossword Game Berbantuan Canva untuk Meningkatkan Kemampuan Berpikir Kritis dan Kreativitas Siswa Kelas 5 SD - Himah, Musabiku Choiriyatul; Oktaviani, Ragil Tri; Amalia, Shofi Nur (Universitas Alma Ata, 2024)
This research aims to develop Science Crossword Game media assisted by Canva to improve the critical thinking and creativity skills of 5th grade students at Zaid Bin Tsabit Creative SDI, Bitar Regency. This research method is research and development Research and Development (R&D). The subject of this research is class 5. The research location is SDI Creative Zaid Bin Thabit, Bitar Regency. Data collection uses observation, interviews, tests, questionnaires, documentation. The data analysis techniques used are the gutmaan scale, Likert scale, and gain score formula. The results of the research show that the development of the Science Crossword Game media assisted by Canva to improve the critical thinking skills and creativity of grade 5 students is as follows: a) The validity and feasibility of the Science Crossword Game media assisted by Canva, the results of material expert validation obtained an overall average of 3.5 with a percentage of 87% is in the